PENGARUH LAMA PENYIMPANAN TERHADAP KARAKTERISTIK MIKROBIOLOGI KEFIR SUSU KAMBING DENGAN EKSTRAK BIJI BUNGA MATAHARI (Helianthus annuus L.) - Putri, Risma; Wulandari, Eka; Pratama, Andry (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
Kefir is a processed product made from milk fermented with various bacteria. In general, kefir is often substituted with plants such as dragon fruit, but it turns out that kefir can also be substituted with grains, one of which is sunflower seeds. However, the optimum storage length of kefir when stored at low temperatures is unknown. This study determined whether storage duration is affected by substituting sunflower seed extract on pH, total lactic acid bacteria, and total yeast. This research was conducted using an experimental method using a completely randomized design (CRD) with 4 treatments based on the length of storage consisting of P1 (No storage), P2 (Day 7), P3 (Day 14), and P4 (Day 21). The data were then analyzed using variance analysis, and the orthogonal polynomial test was continued. The results showed that the length of storage of kefir with substitution of sunflower seed extract at refrigeration temperature for 21 days showed that the pH value was not significantly different, while the total bacteria and total lactic acid were significantly different with a cubic regression pattern y = 0.0003x3 - 0.0142x2 + 0.1755 + 8.164x for total lactic acid bacteria and y = 0.0005x3 - 0.017x2 + 0.1796x + 8.3634 for total yeast so that the optimum storage length of kefir with sunflower seed extract substitution is obtained on day 8.